Characterization of white matter changes along fibers by automated fiber quantification in the early stages of Alzheimer's disease - Zhang, Xin; Sun, Yu; Li, Weiping; Liu, Bing; Wu, Wenbo; Zhao, Hui; Liu, Renyuan; Zhang, Yue; Yin, Zhenyu; Yu, Tingting; Qing, Zhao; Zhu, Bin; et al. (NeuroImage. Clinical, 2019)
Brain white matter fiber bundles in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) have abnormalities not usually seen in unaffected subjects. Ideal algorithm of the localization-specific properties in white matter integrity might reveal the changes of tissue properties varying along each tract, while previous studies only detected the mean DTI parameters of each fiber. The aim of this study was to investigate whether these abnormalities of nerve fiber tracts are localized to specific regions of the tracts or spread throughout and to analyze which of the examined fiber tracts are involved in the early stages of Alzheimer's disease. In this study, we utilized VBA, TBSS as well as AFQ together to comprehensively investigate the white matter fiber impairment on 25 CE patients, 29 MCI patients and 34 normal control (NC) subjects. Two tract profiles, fractional anisotropy (FA) and mean diffusivity (MD), were extracted to evaluate the white matter integrity at 100 locations along each of 20 fiber tracts and then we validated the results with 27 CE patients, 21 MCI patients and 22 NC from the ADNI cohort. Also, we compare the AFQ with VBA and TBSS in our cohort. In comparison with NC, AD patients showed widespread FA reduction in 25% (5 /20) and MD increase in 65%(13/20) of the examined fiber tracts. The MCI patients showed a regional FA reduction in 5% (1/20) of the examined fiber tracts (right cingulum cingulate) and MD increase in 5%(1/20) of the examined fiber tracts (left arcuate fasciculus). Among these changed tracts, only the right cingulum cingulate showed widespread disruption of myelin or/and fiber axons in MCI and aggravated deterioration in AD, findings supported by FA/MD changes both by the mean and FA changes by point wise methods and TBSS. And the AFQ findings from ADNI cohort showed some similarity with our cohort, especially in the pointwise comparison of MD profiles between AD vs NC. Furthermore, the pattern of white matter abnormalities was different across neuronal fiber tracts; for example, the MCI and AD patients showed similar FA reduction in the middle part of the right cingulum cingulate, and the anterior part were not damaged. However, the left arcuate fasciculus showed MD elevation located at the temporal part of the fibers in the MCI patients and expanding to the temporal and middle part of the fibers in AD patients. So, the AFQ may be an alternative complementary method of VBA and TBSS, and may provide new insights into white matter degeneration in MCI and its association with AD.
Keywords: Mild cognitive impairment; interpretace obrazu počítačem; zobrazování difuzních tenzorů; Female; Automated fiber quantification; Diffusion tensor imaging; Image Interpretation, Computer-Assisted; ženské pohlaví; Pointwise comparison; White Matter; lidé; Aged, 80 and over; Alzheimer's disease; Male; Aged; Alzheimer Disease; Diffusion Tensor Imaging; Alzheimerova nemoc; lidé středního věku; Nerve Fibers; senioři nad 80 let; nervová vlákna; senioři; mužské pohlaví; Middle Aged; bílá hmota; Humans